Edukasi Gizi dalam Pelayanan Kebidanan Komunitas sebagai Upaya Peningkatan Kesehatan Ibu dan Anak Melalui Pendidikan Keluarga - Bernadeta Erni; Diah Ayu Dwi Satiti; Windy A. V. Fanggi; Filpin L.A. Haning; Oktaviana T.M.B. Adam; Ni Putu I. D. P. Murti (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Health issues are complex and require new ideas for their resolution. Public health focuses on disease prevention, health promotion, and physical, mental, and social therapy. Maternal and Child Health (MCH) and women’s health throughout their life cycle are crucial public health issues as they have a significant impact on the quality of human resources in a generation. In Pukdale Village, East Kupang District, Kupang Regency, problems such as the lack of knowledge among pregnant women about Chronic Energy Deficiency (CED), pregnancy anemia, Exclusive Breastfeeding (EBF), balanced nutrition, and weaning have been identified. To address these issues, a Community Midwifery Care program based on community service was carried out, which included counseling, training, demonstrations, and simulations. The results of this activity showed a positive response and active participation from the community in Pukdale Village in the programs implemented by the students. There was a significant improvement in the knowledge of pregnant women about CED, pregnancy anemia, EBF, as well as the knowledge of mothers of infants about balanced nutrition and weaning. This is expected to improve the overall health status of the community in the village.